2003
DOI: 10.1128/jvi.77.16.9029-9040.2003
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Class I Alleles Associated with Slow Simian Immunodeficiency Virus Disease Progression Bind Epitopes Recognized by Dominant Acute-Phase Cytotoxic-T-Lymphocyte Responses

Abstract: Certain major histocompatibility complex class I (MHC-I) alleles are associated with delayed disease progression in individuals infected with human immunodeficiency virus (HIV) and in macaques infected with simian immunodeficiency virus (SIV). However, little is known about the influence of these MHC alleles on acute-phase cellular immune responses. Here we follow 51 animals infected with SIVmac239 and demonstrate a dramatic association between Mamu-A*01 and -B*17 expression and slowed disease progression. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
180
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(193 citation statements)
references
References 72 publications
10
180
2
1
Order By: Relevance
“…These investigations revealed a new association of Mauritian MHC haplotype and susceptibility/resistance to SHIV 89.6P infection. The association of particular MHC alleles with resistance of rhesus macaques to SIV and SHIV infection is well established [38][39][40][41][42][43]. Our results here extend the phenomenon to cynomolgus macaques of Mauritian origin.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…These investigations revealed a new association of Mauritian MHC haplotype and susceptibility/resistance to SHIV 89.6P infection. The association of particular MHC alleles with resistance of rhesus macaques to SIV and SHIV infection is well established [38][39][40][41][42][43]. Our results here extend the phenomenon to cynomolgus macaques of Mauritian origin.…”
Section: Introductionsupporting
confidence: 81%
“…HLA-B*27 and B*57 are associated with delayed AIDS progression, while HLA-B*35 is associated with accelerated AIDS onset [57]. In rhesus macaques, Mamu-B*17 is associated with reduced plasma viremia and slowed disease progression following infection with SIV mac239 [40,42], although by itself it does not guarantee better disease outcome [58]. Mamu-B*08 positive rhesus macaques display reduced chronic phase viremia following SIV mac239 infection, and the allele is overrepresented in elite controllers [38].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Major histocompatibility complex (MHC) class I antigens that present foreign peptides can activate cytotoxic T lymphocytes (CTL), which are crucial for containing viral replication. Several studies have shown (1) a temporal relationship between the decline of viral load and the emergence of CTL responses in both infected humans and infected monkeys, [3][4][5][6] (2) an increase of viral load after the appearance of CTL-escape HIV/SIV mutants during chronic and acute infection [7][8][9][10][11][12][13] and (3) a dramatic rise of viral load after CD8 þ T-cell depletion. [14][15][16] Additional indirect evidence for a CTL effect upon viral replication came from genetic association studies showing that Mhc class I alleles are strongly associated with survival time in HIV-infected humans [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that single MHC antigens such as Mamu-A*01 and -B*17 are significantly associated with prolonged survival in SIV-infected rhesus macaques. 13,[25][26][27] However, monkeys sharing one or two of these MHC antigens may still exhibit a variable course of disease. 27,28 We therefore assessed the association between Mhc class I haplotypes, rather than single gene variants, and survival time in SIV-infected rhesus macaques.…”
Section: Introductionmentioning
confidence: 99%
“…We were unable to determine the major histocompatibility complex (MHC) type of the Chinese monkeys with the currently available reagents. 54 These reagents are thus effective only for MHC type of Indian monkeys, suggesting that these populations are genetically distinct. In this context, Ling et al 55 reported that Chinese rhesus monkeys more closely resemble humans than Indian monkeys do in terms of viral load and CD4 T-cell count following retroviral infection.…”
Section: Prophylactic Vaccinementioning
confidence: 99%